Introducing Gamification Methods To High School Student At Bina Nusantara University Alam Sutera - Arsa Widitiarsa Utoyo (Journal of Games, Game Art, and Gamification, 2018)
Exploration studies in this article highlighted approaches that wearable to increase the value of gamification method to examine the impact of the role of facilitator in the idea of the group. Through the activities, the children of high school/high school were invited as respondents. This activity aimed to stimulate creativity to produce a different settlement with the same results. The presentation material and workshops that used materials of paper and stationeries. Finally, this article outlines recommendations for teaching, learning, and apply gamification in decision making. This method is one of the modern methods of teaching and learning. It starts with forming groups, job descriptions, and the active participation of the students and by comparing the characteristics of the method by the way students learn gamification, the positive effects of this method on the educational attainment of students confirmed.Â Based on the finding of the study the researcher recommended encouraging faculty members to use gamification strategy in teaching, conducting more studies discussing this strategy and its relation to other variables such as critical thinking, conducting more studies on other samples from different study and age levels and from different environments.Â Keywords: gamification method, student, creativity, university students